Integrating defensible space in public high schools in Davao City a study on passive crime control and perception of safety - Gido, Omar Alexis B. (2019)
"The feeling of safety highly influences passive crime prevention. The feeling or perception of safety is directly influenced by the presence of elements of design that claims a particular territory, and inherits surveillance and presents an identified image as was described by the Defensible Space Theory by Oscar Newman.The presence and absence of design and the elements of design greatly affects the behavioral patterns of users in a particular area. With the proper use of the elements and environmental design of the defensible space theory would greatly affect the behavior of students making them feel safe and at the same time refrain from doing delinquent activities and violations. The study revolves around the foundation of the Defensible Space Theory and its architectural application on public school design in Davao City.The correlation between the feeling of safety and the site and environmental quality of school designs were assessed across public secondary schools in Davao city. The data showed a positive moderate correlation between the two parameters. The data showed that a school site and built-up design which follows the principle and ideals of the Defensible Space Theory has a positive effect on passive crime and juvenile delinquencies on public schools that would lead to a holistic schooling experience and vital development of students."